On the metabolism of benzoic acid by cows on purified protein-free and low-protein feed - Kreula, M.; Rauramaa, A.; Tegengren, M. (Agricultural and Food Science, 1978)
Two test cows, one adapted to purified, protein-free feed (0-feed, 0-cow) and the other to a low-protein feed (ULP-feed, ULP-cow) in which 60 % of the nitrogen was derived from urea, were fed single doses of 212 and 193 µCi [ring U-14C] benzoic acid respectively in 0.01 % benzoic acid solution. For five days the milk, faeces and urine were collected quantitatively. Fat, protein and lactose contents of the milk samples were determined and these components were isolated in pure form. 23.5 and 98.8 % respectively of the 14C-activity given to the 0- and ULP-cows was found in the urine, and 2.5 % and 3.0 % in the faeces. Totals of 0.5 % and 0.8 % were recovered in the milk, as found from analyses of whole milk. The sum of the activities in isolated fat, protein and lactose components was 0.2 % for both cows, and only the protein being labelled.